Contrasting 'smart mobility' and 'sustainable mobility' in transport governance: The case of municipalities in Estonia - Mihhail Kirejev; Wolfgang Dieter Gerstlberger; Tarvo Niine (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
Modern cities are developing exponentially and thus ensuring mobility is one of the key challenges. The solution can be viewed as the determination of optimal vectors of strategic city development, including transport as a sub-system. One dominant theme in respective research discourse is sustainable mobility. A competing concept, 'smart mobility', is fuelled by on-going ICT development, aiming to bring about urban transformation with a data-driven approach. While, to a certain extent, smart approach does provide improvement to quality and efficiency of urban life, resulting also in contribution to sustainability goals, then in terms of philosophical foundation, it appears rather an input-driven approach, whereas the logic of sustainable mobility is driven foremost by outputs. Therefore, in this study, the two approaches are treated as two distinct development vectors. Estonia is a pioneer of digital innovation, so the local transport development can be similarly assumed to be ICT-infused. Our study observes the detailed nature of transport system governance and aims to identify the relationships between smart and sustainable paradigms. The study analyses the governance paths of urban transport systems in a sample of medium and small municipalities in Estonia, by evaluating explicit development strategies. The ensuing analysis of expert interviews using a quasi-binary method contributes to the scientific discussion on the smart and sustainable balance and co-existence with empirical insights to policymakers. The study indicates that a local transport governance paradigm is not only influenced mainly by local socio-economic characteristics and environmental factors but also notably on the competence, knowledge, skills and beliefs of incumbent officials. Furthermore, the established relations between smart and sustainable development indicators provides a basis for assessing balance in transport development concepts, as it is possible to consider the integrated concept 'smart and sustainable' as a paradigm evolution.
Keywords: G38; R58; Q01; R11; 330; Smart City; Smart Transport Development; Sustainable Urban Development; Smart And Sustainable Governance; Smart Mobility